MODERASI BERAGAMA: REORIENTASI NILAI TOLERANSI DALAM IMPLEMENTASI KURIKULUM PAI - Andini Nur Afifih; Rani Diana Putri; Mazro’atul Maslachah; Ni’matul Waladiyah; Ali Sodikin (Pascasarjana PAI Multikultural Universitas Yudharta Pasuruan, 2026)
This study aims to analyze the relevance of religious tolerance values in the implementation of the Islamic Religious Education (PAI) curriculum at UPT SMP Negeri 24 Gresik. The study focuses on how tolerance values are integrated into PAI learning, the strategies used by teachers in instilling tolerance values, as well as the supporting and inhibiting factors in their implementation. This research employed a qualitative approach with a descriptive case study design. Data were collected through observation, interviews, and documentation. The informants consisted of Islamic Religious Education teachers, the principal, students, and other relevant parties. Data analysis was conducted using the interactive model of Miles and Huberman, including data reduction, data presentation, and conclusion drawing. The validity of the data was ensured through source triangulation and technique triangulation. The results of the study indicate that the implementation of religious tolerance values at UPT SMP Negeri 24 Gresik has been integrated into the PAI learning process through contextual learning materials related to respecting differences, living harmoniously, and maintaining good social relationships. Teachers applied discussion methods, question-and-answer sessions, group work, and dialogical approaches to foster students’ tolerance attitudes. The findings also show that students demonstrated tolerant behavior in their social interactions, such as cooperating, respecting others, and maintaining harmonious relationships with peers. Supporting factors in implementing tolerance values include a conducive school environment, positive school culture, teachers’ role models, and collaboration between schools and parents. Meanwhile, inhibiting factors include differences in students’ character and understanding, external environmental influences, and the impact of social media. Therefore, continuous character education and collaboration between schools, families, and communities are needed to strengthen the implementation of religious tolerance values in schools.